Deformation of the shaft in torsion and the effect of torsion along with bending - Obidov, Avazbek; Mirzaumidov , Asilbek; Abdurasulov , Axrorbek; Otaqoʻziyev , Doniyorjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Insufficient smoothness of the saw cylinder shaft leads to impermissible misalignments in the gap between the columns, which has a very negative effect on the grinding process. In this case, using the method of equivalent diameters developed by B.P. Jemochkin, we determine the bending and turning angles of the saw cylinder shaft.